Investigation on Fatigue Resistance of Asphalt Mixture Containing Crumb Rubber - Abu Hassan Shaari, Muhammad Afiq; Buhari, Rosnawati (Recent Trends in Civil Engineering and Built Environment, 2023)
The increase of this disposal waste tire surely will increase the amount of waste tires at stockpiled or landfill that can threated the human health and environment nearer to the landfill area. In addition, nowadays utilization of waste product in construction industry is going rapidly. Crumb Rubber Powder (CRP) is the one type of waste product which produced in the waste or broken tire from the process of ambient granulating and cryogenic grinding. In this study, CRP was utilized in the Hot Mix Asphalt (HMA) as added material mineral by 1%, 2%, & 3% replacement of the total mixture on the conventional HMA. For this study CRP content that utilized in asphalt mixtures. The mechanical properties were evaluated by Marshall Mix on volumetric test, Indirect Tensile Fatigue Test (ITFT), Softening point of bitumen and Penetration of bitumen. On this result for this study, it produced about 0% of CRP added in HMA will reach the greatest result of fatigue resistance compared to the added CRP in HMA. Then, on 2% of mixture that will conduct the lowest fatigue cracking that due to the lowest number cycles and low deformation (mm). Next, it can be determining that by the previous studies the highest percent replacement added content of CRP will conduct the lowest performance of fatigue resistance at 2% added compare to the conventional HMA of asphalt mixture.